700 DEG C high-temperature titanium alloy for medium and short time and preparation method thereof
By accurately controlling the element content and performing specific solution treatment in the titanium alloy, the fine sheet layer structure with fine original β grains is formed, which solves the problem of insufficient performance in the existing high-temperature titanium alloy at above 700°C in a short time, and achieves high tensile strength, yield strength and high temperature durability.
Patent Information
- Application Number
- CN202411536900.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-28
AI Technical Summary
The existing high-temperature titanium alloys have insufficient medium- and short-term performance at above 700°C, especially in the applications of lightweight structural parts such as high-Mach number aircraft wings and rudders, which are difficult to meet the needs of extreme high temperature resistance and high strength.
By precisely controlling the mass percentage of elements such as Al, Sn, Zr, Mo, Nb, Si, W, Ti, etc. in the titanium alloy, especially increasing the content of Zr and Si, forming a composite solid solution, increasing the dissolution temperature of the silicide, and performing solid solution treatment above the β phase transition point and below the silicide dissolution temperature to obtain fine sheet structure with fine original β grains.
It realizes the high tensile strength and yield strength of titanium alloy at 700℃, and also has good medium and short-term high temperature durability and fracture toughness, meeting the demand of high Mach number aircraft for extreme high temperature resistance (700℃) high-strength titanium alloys.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium alloy processing, and in particular to a 700°C high-temperature titanium alloy for medium and short-term use and a preparation method thereof. Background Art
[0002] With the development of aerospace technology, the demand for aircraft is increasing. Aircraft need to overcome gravity during operation and serve in complex environments such as high temperature and high speed, so the requirements for lightweight components are extremely high. Titanium alloy has become the preferred material for aircraft due to its high specific strength and low density. Unlike traditional titanium alloys that pursue high creep, fatigue and thermal stability, aerospace vehicles require high-strength titanium alloys with medium and short-term extreme high temperature resistance.
[0003] With the advancement of science and technology, the operating temperature range of high-temperature titanium alloys has been significantly improved, from the initial 350°C to 650°C. The strengthening of titanium alloys is mainly achieved through solid solution strengthening and the introduction of silicon. However, as the temperature continues to increase, traditional strengthening methods have reached their limits. In order to increase the operating temperature of titanium alloys, some researchers have proposed a medium- and short-term high-temperature titanium alloy of 650 to 700°C and its preparation method, but the plasticity of the parts is low, and the medium- and short-term high-temperature durability and fracture toughness are not involved. Some researchers have also designed a short-term high-temperature resistant titanium alloy with excellent high-temperature mechanical properties, but it can only meet the medium- and short-term performance of 650°C without involving 700°C.
[0004] Recently, there has been an urgent demand for high-strength titanium alloys with extreme high-temperature resistance (700°C) for short and medium-term lightweight structural parts such as wings and rudders of high-Mach number aircraft. There is an urgent need to explore new methods that can withstand high temperatures of 700°C and have certain high-temperature mechanical properties. Summary of the invention
[0005] In view of the above analysis, the embodiments of the present invention aim to provide a 700°C high-temperature titanium alloy for medium and short-term use and a preparation method thereof, so as to meet the urgent demand for medium and short-term extreme high-temperature resistant (700°C) high-strength titanium alloys for lightweight structural parts such as wings and rudders of high Mach number aircraft.
[0006] On the one hand, an embodiment of the present invention provides a 700°C high temperature titanium alloy for medium and short time use, comprising, by weight percentage, Al: 5.5-6.5%, Sn: 3.0-5.0%, Zr: 5.0-8.0%, Mo: 0.5-1.5%, Nb: 0.2-1.0%, Si: 0.6-0.8%, W: 1.0-2.0%, and the balance is Ti;
[0007] The medium and short-term use of 700℃ high temperature titanium alloy, room temperature tensile strength R m ≥1120MPa, yield strength R p0.2≥1010MPa, elongation A≥8%, section shrinkage Z≥10%; tensile strength R at 700℃ m ≥610MPa, yield strength R p0.2 ≥470MPa, elongation A≥20%, section shrinkage Z≥50%.
[0008] On the other hand, an embodiment of the present invention provides a method for preparing a 700°C high temperature titanium alloy for medium and short time use, which is used to prepare the above-mentioned 700°C high temperature titanium alloy for medium and short time use, and the preparation method comprises the following steps:
[0009] S1, after vacuum consumable smelting for 3 times, an alloy ingot is obtained;
[0010] S2, subjecting the alloy ingot to a first stage of deformation;
[0011] S3, subjecting the alloy ingot to a second stage of deformation;
[0012] S4, solution and aging heat treatment, finally obtaining a 700℃ high temperature titanium alloy for medium and short time use;
[0013] Furthermore, in S1, the raw materials added during smelting include, by weight percentage, Al: 5.5-6.5%, Sn: 3.0-5.0%, Zr: 5.0-8.0%, Mo: 0.5-1.5%, Nb: 0.2-1.0%, Si: 0.6-0.8%, W: 1.0-2.0%, and the balance is Ti.
[0014] Furthermore, in S1, alloy elements Sn, Zr, Mo, Si, Nb, and W are all added in the form of intermediate alloys during smelting; the Al portion is brought in by the intermediate alloy, and the insufficient portion is added in the form of high-purity Al beans and Al foils; the insufficient portion of Ti is added in the form of titanium sponge.
[0015] Furthermore, in S2, the first stage deformation is to heat the ingot to 20-150°C above the β phase transformation point, keep it warm for a period of time, and then perform 2-4 fires of open forging, each fire deformation is 1-2 times of upsetting and drawing, and the deformation amount of upsetting and drawing is 30-60%.
[0016] Furthermore, the β phase transition point is 1030-1045°C.
[0017] Furthermore, in S3, the second stage of deformation is to heat the ingot to 60-20°C below the β phase transformation point, keep it warm for a period of time, and then perform 2-7 fires of forging or die forging; wherein, the deformation before the last fire is 1-2 times of upsetting and drawing, and the deformation of upsetting and drawing is 30-60%; the last fire is upsetting and drawing, drawing or die forging, and the deformation is 30-70%. If it is die forging, the strain rate should be controlled at 0.01-0.1s-1 , after conversion, they are all air-cooled.
[0018] Furthermore, in S4, the solution treatment controls the solution temperature between the β phase transition point and the silicide dissolution temperature, keeps the temperature for 2 to 5 hours, and then cools with water or quenches with oil; the silicide dissolution temperature is 1050 to 1065°C.
[0019] Furthermore, in S4, the aging treatment is carried out at a temperature of 700-750° C., and is kept at this temperature for 5-6 hours before being air-cooled.
[0020] Furthermore, in S4, if the difference between the silicide dissolution temperature and the β phase transition point is ≥30°C, the solid solution temperature is selected to be 20°C above the β phase transition point; if the difference between the silicide dissolution temperature and the β phase transition point is between 20 and 30°C, the solid solution temperature is selected to be 10°C above the β phase transition point; if the difference between the silicide dissolution temperature and the β phase transition point is ≤20°C, the solid solution temperature is selected to be 5°C below the silicide dissolution temperature.
[0021] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0022] 1) The 700℃ high-temperature titanium alloy for medium and short-term use provided by the present invention can increase the dissolution temperature of silicide to above the β phase transition point by precisely controlling the mass percentage of elements such as Al, Sn, Zr, Mo, Nb, Si, W, and Ti in the titanium alloy, especially controlling the content of Zr and Si elements, and can be subjected to solid solution treatment above the β phase transition point and below the dissolution temperature of silicide, thereby ensuring that the high-temperature titanium alloy can withstand a high temperature of 700℃ and has certain medium and short-term high-temperature durability and fracture toughness. It can meet the demand for medium and short-term extreme high-temperature resistant (700℃) high-strength titanium alloy.
[0023] 2) Compared with the existing high-temperature titanium alloys, the present invention increases the content of Zr and Si. Zr and Si can coexist in the solid solution of the titanium alloy to form a composite solid solution with higher stability and solubility, which helps to increase the dissolution temperature of silicide to above the β phase transition point, allowing silicide to participate in deformation and solution treatment, and utilize silicide to inhibit grain growth, effectively solving the problem of coarse grains caused by β heat treatment, obtaining fine original β grains, and providing a compositional basis for subsequent thermomechanical treatment.
[0024] 2) Compared with the existing high-temperature titanium alloy, the present invention eliminates the addition of expensive elements such as Ta and Hf, thereby achieving the purpose of reducing costs while obtaining higher temperature resistance.
[0025] 3) The present invention increases the dissolution temperature of silicide to above the β phase transition point by increasing the content of Zr and Si. Solution treatment can be performed in a narrow range above the β phase transition point and below the dissolution temperature of silicide to obtain a fine lamellar structure with original β grains. The fine original β grains abandon the weaknesses of low plasticity, low cycle fatigue and large data dispersion of traditional lamellar structures, which helps to reduce stress concentration, reduce the occurrence of cracks, and improve the plasticity, fatigue resistance and other properties of the material. It is expected to be used for a short time at 700°C or for a long time under coating protection.
[0026] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0028] Figure 1 The fine lamellar structure of the dispersed precipitated silicide in Example 1 of the present invention;
[0029] Figure 2 This is the fine lamellar structure of the original β grains in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.
[0031] On the one hand, a specific embodiment of the present invention discloses a 700°C high temperature titanium alloy for medium and short time use, comprising, by weight percentage, Al: 5.5-6.5%, Sn: 3.0-5.0%, Zr: 5.0-8.0%, Mo: 0.5-1.5%, Nb: 0.2-1.0%, Si: 0.6-0.8%, W: 1.0-2.0%, and the balance is Ti;
[0032] The medium and short-term use of 700℃ high temperature titanium alloy, room temperature tensile strength R m ≥1120MPa, yield strength R p0.2 ≥1010MPa, elongation A≥8%, section shrinkage Z≥10%; tensile strength R at 700℃ m ≥610MPa, yield strength R p0.2≥470MPa, elongation A≥20%, section shrinkage Z≥50%.
[0033] The following is a detailed description of the effects and dosage of the components in the present invention:
[0034] Zr: Zirconium can enhance the strength and creep resistance of titanium alloys in high temperature environments, and can also refine the grain structure to improve the strength and toughness of the alloy. When the Zr content is too low, this refinement effect may be insufficient. When the Zr content is too high, it may cause uneven grain size. Conventional high-temperature titanium alloys generally control Zr within 5%. The present invention increases the Zr content to 5.0-8.0%. A higher content of Zr helps to form a composite solid solution with Si, dissolve silicide more effectively, and increase its dissolution temperature. The dissolution temperature of silicide can be increased to above the β phase transition point, so that silicide participates in deformation and solution treatment, and silicide is used to inhibit grain growth to obtain fine original β grains, thereby improving the strength, durability, fracture toughness and other properties of titanium alloys.
[0035] Si: Silicon element can affect the strength and plasticity of titanium alloy at room temperature and high temperature. An appropriate amount of Si can improve the high temperature strength of the alloy, but when it exceeds a certain content, the plasticity of the alloy may be reduced. Si element is added to most high temperature titanium alloys, but generally not more than 0.5%. The present invention increases the Si content to 0.6-0.8%. A higher content of Si is easy to form a more stable substance with Zr and Ti, thereby raising the silicide dissolution temperature to above the β phase transition point, and then through solution treatment above the β phase transition point and below the silicide dissolution temperature, the fine lamellar structure of the original β grains is obtained. The fine grains help to reduce stress concentration, reduce the generation of cracks, and provide a compositional basis for subsequent thermomechanical treatment.
[0036] Al: Aluminum, as an α-stabilizing element, can significantly improve the room temperature and high temperature strength and thermal strength of titanium alloys through solid solution strengthening. Therefore, the addition of Al at high temperatures helps to maintain the strength and creep resistance of the alloy. In addition, at high temperatures, the Al element tends to combine with oxygen to form stable Al2O3, which can provide a certain degree of antioxidant protection for the alloy. However, when the Al content is low (such as less than 5%), the Al2O3 oxide film formed may not be continuous enough, thereby affecting its antioxidant properties. Therefore, in order to ensure that the titanium alloy has good strength, creep resistance and antioxidant properties, the Al content in the titanium alloy of the present invention is controlled at 5.5-6.5%.
[0037] Sn: Tin, as an α-stabilizing element, can improve the strength of the material by solid solution in the α phase of the titanium alloy. This strengthening effect is still effective at high temperatures, enhancing the strength and creep resistance of the titanium alloy in high temperature environments. In addition, the addition of Sn can refine the grain structure of the titanium alloy, and grain refinement helps to improve the strength and toughness of the alloy. Studies have shown that when the Sn addition reaches a certain value (such as 4%), the yield strength and tensile strength of the alloy reach a peak. However, when the Sn content continues to increase (such as exceeding 6%), the yield strength and tensile strength begin to decrease slightly. Therefore, in order to ensure that the titanium alloy has good yield strength and tensile strength, the Sn content in the titanium alloy of the present invention is controlled at 3.0-5.0%.
[0038] Mo: Molybdenum can refine the grain structure of the alloy and improve the strength and toughness of the alloy. In addition, it can also improve the strength of the material by dissolving in the β phase of the titanium alloy, especially at high temperatures, where the strengthening effect is more obvious. An appropriate amount of molybdenum can improve the properties of titanium alloys, including strength, plasticity, corrosion resistance and thermal stability. When the content of Mo element is too high (such as more than 3%), segregation may occur inside the titanium alloy, causing more Al element to be dissolved in the α phase. Therefore, the content of Mo in the titanium alloy of the present invention is controlled at 0.5-1.5%. Within this range, the Mo element can balance the mechanical properties and thermal stability of the alloy, improve the structure and performance of the titanium alloy, and avoid excessive costs and adverse effects.
[0039] Nb: Niobium can improve the strength of the material by dissolving in the β phase of the titanium alloy, and can work synergistically with other elements to form a stable microstructure, thereby improving the thermal stability of the alloy. In addition, an appropriate amount of Nb can refine the grain structure of the alloy and improve the strength and toughness of the alloy. However, as the Nb content increases (such as exceeding 2%), the α layer in the titanium alloy may become thicker, resulting in coarsening of the structure, affecting the mechanical properties and high temperature stability of the titanium alloy. Therefore, the Nb content in the titanium alloy of the present invention is controlled at 0.2-1.0%.
[0040] W: Tungsten can improve the strength of the material by dissolving in the β phase of the titanium alloy, and can synergize with other elements to form a stable microstructure, thereby improving the thermal stability of the alloy. In addition, an appropriate amount of W can refine the grain structure of the alloy and improve the strength and toughness of the alloy. However, too much W will lead to a significant increase in the residual β phase content in the alloy and a significant refinement of the size of each phase, thereby reducing the yield strength of the titanium alloy; when the content of W is too low, its strengthening effect cannot be fully exerted. In order to balance the mechanical properties and thermal stability of the alloy, the W content in the titanium alloy of the present invention is controlled at 1.0-2.0%.
[0041] It should be noted that conventional high-temperature titanium alloys, such as 600-650℃ high-temperature titanium alloys, are mostly designed to meet the need for long-term high-temperature resistance, so Ta or Hf are added with a higher mass fraction, and the high-temperature creep and fatigue properties of the alloy are improved by the strengthening and oxidation resistance of Ta, Hf and other elements to increase the high-temperature resistance time. However, elements such as Ta and Hf are expensive and have high preparation costs.
[0042] The titanium alloy designed by the present invention is used as a high-strength titanium alloy with extreme high temperature resistance (700°C) for a medium to short time (usually no more than 20 hours). The present invention does not need to add expensive elements such as Ta and Hf, and achieves the purpose of reducing costs while obtaining higher temperature resistance.
[0043] In addition, the microstructure of traditional high-temperature titanium alloys is mostly lamellar. This structure can provide better strength and hardness in some cases, but it still has weaknesses such as low plasticity, low cycle fatigue and large data dispersion. In order to overcome these weaknesses, the present invention improves the material performance by obtaining fine lamellar structures of original β grains. Fine original β grains help reduce stress concentration and crack generation, thereby improving the plasticity, fatigue resistance and other properties of the material.
[0044] Furthermore, in order to obtain the fine lamellar structure of the original β grains, the temperature of the solution treatment needs to be precisely controlled to ensure that the alloy elements are fully dissolved and form a fine grain structure. Usually, the solution treatment needs to be performed above the β phase transition point and below the silicide dissolution temperature. Heating above the β phase transition point can obtain a lamellar structure, but the grains will be unconstrained and will grow abnormally. It is also necessary to control the temperature below the silicide dissolution temperature to use silicide to limit grain growth.
[0045] The dissolution temperature of traditional titanium alloy silicide is lower than the β phase transformation point, so the fine lamellar structure of the original β grains cannot be obtained.
[0046] The present invention increases the content of Zr and Si in the alloy. Zr and Si can coexist in the solid solution of the titanium alloy to form a composite solid solution. This composite solid solution has higher stability and solubility, which helps to increase the dissolution temperature of the silicide to above the β phase transition point. Then, by solution treatment above the β phase transition point and below the dissolution temperature of the silicide, the fine lamellar structure of the original β grains (the original β grains are ≤500mm, and the lamellar thickness is less than or equal to 5μm) is obtained, which provides a composition basis for subsequent thermomechanical treatment.
[0047] On the other hand, a specific embodiment of the present invention discloses a method for preparing a 700°C high temperature titanium alloy for medium and short time use, which is used to prepare the above-mentioned 700°C high temperature titanium alloy for medium and short time use, and the preparation method comprises the following steps:
[0048] S1, after vacuum consumable smelting for 3 times, an alloy ingot is obtained;
[0049] S2, subjecting the alloy ingot to a first stage of deformation;
[0050] S3, subjecting the alloy ingot to a second stage of deformation;
[0051] S4, solid solution and aging heat treatment, finally obtain 700℃ high temperature titanium alloy for medium and short time use.
[0052] Furthermore, in S1, the raw materials added during smelting include, by weight percentage, Al: 5.5-6.5%, Sn: 3.0-5.0%, Zr: 5.0-8.0%, Mo: 0.5-1.5%, Nb: 0.2-1.0%, Si: 0.6-0.8%, W: 1.0-2.0%, and the balance is Ti.
[0053] Furthermore, in S1, alloy elements Sn, Zr, Mo, Si, Nb, and W are all added in the form of intermediate alloys during smelting; the Al portion is brought in by the intermediate alloy, and the insufficient portion is added in the form of high-purity Al beans and Al foils; the insufficient portion of Ti is added in the form of titanium sponge.
[0054] Specifically, in S1, during smelting, the alloy package is distributed and the electrodes are pressed, and the electrode blocks are welded for vacuum consumable smelting.
[0055] Furthermore, in S2, the first stage deformation is to heat the ingot to 20-150°C above the β phase transformation point, keep it warm for a period of time, and then perform 2-4 fires of open forging, each fire deformation is 1-2 times of upsetting and drawing, and the deformation amount of upsetting and drawing is 30-60%.
[0056] Furthermore, in S2, the β phase transition point is 1030-1045°C.
[0057] Specifically, the β phase transition point is determined by GB / T 23605 (Method for determining β transition temperature of titanium alloy) or HB 6623.2 (Method for determining β transition temperature of titanium alloy - Metallographic method).
[0058] Furthermore, in S3, the second stage of deformation is to heat the ingot to 60-20°C below the β phase transformation point, keep it warm for a period of time, and then perform 2-7 fires of forging or die forging; wherein, the deformation before the last fire is 1-2 times of upsetting and drawing, and the deformation of upsetting and drawing is 30-60%; the last fire is upsetting and drawing, drawing or die forging, and the deformation is 30-70%. If it is die forging, the strain rate should be controlled at 0.01-0.1s -1 , after conversion, they are all air-cooled.
[0059] Specifically, in S2 and S3, due to the composition design of the present invention, the dissolution temperature of silicide is above the β phase transformation point, so when heating to the β single-phase region for ingot casting, or even in the heating stage of the α+β two-phase region for forging, the silicide will not dissolve, and can maintain its state as the second phase, pinning the original β grains and preventing them from growing excessively during the heating process. Combined with subsequent deformation and recrystallization, the fine structure of the original β grains is obtained, laying the foundation for the subsequent fine lamellar structure control.
[0060] Furthermore, in S4, the solution treatment controls the solution temperature between the β phase transition point and the silicide dissolution temperature, and is kept warm for 2 to 5 hours before being water-cooled or oil-quenched.
[0061] Specifically, in order to obtain the fine lamellar structure of the original β grains, it is not only necessary to heat the temperature of the solution treatment to above the β phase transformation point to obtain the lamellar structure, but also necessary to control the temperature below the silicide dissolution temperature, using silicide to inhibit abnormal grain growth and obtain the fine lamellar structure of the original β grains.
[0062] The dissolution temperature of traditional titanium alloy silicide is lower than the β phase transition point, so it is impossible to obtain the fine lamellar structure of the original β grains. The present invention increases the content of Zr and Si. The higher content of Zr and Si coexists in the solid solution of the titanium alloy to form a composite solid solution. This composite solid solution has higher stability and solubility, and increases the dissolution temperature of silicide to above the β phase transition point.
[0063] Furthermore, in S4, the silicide dissolution temperature is 1050-1065°C.
[0064] Specifically, the silicide dissolution temperature can refer to the metallographic method in GB / T 23605 (determination method of β-transformation temperature of titanium alloy) or HB6623.2 (metallographic method for determination method of β-transformation temperature of titanium alloy), and auxiliary reference can be made to the determination of differential thermal analysis method in HB 6623.1 (differential thermal analysis method for determination method of β-transformation temperature of titanium alloy).
[0065] Furthermore, in S4, the aging treatment is carried out at a temperature of 700-750° C., and is kept at this temperature for 5-6 hours before being air-cooled.
[0066] Furthermore, in S4, if the difference between the silicide dissolution temperature and the β phase transition point is ≥30°C, the solid solution temperature is selected to be 20°C above the β phase transition point; if the difference between the silicide dissolution temperature and the β phase transition point is between 20 and 30°C, the solid solution temperature is selected to be 10°C above the β phase transition point. At this time, Class III furnace should be selected with reference to GJB 509B-2008 (heat treatment process quality control); if the difference between the silicide dissolution temperature and the β phase transition point is ≤20°C, the solid solution temperature is selected to be 5°C below the silicide dissolution temperature. At this time, Class II furnace should be selected with reference to GJB509B-2008.
[0067] Specifically, in S4, during the aging treatment, Zr and Si elements will precipitate in the form of fine and evenly distributed silicides and pin on the grain boundaries as second phase particles, effectively inhibiting the growth of grains, thereby obtaining fine original β grains.
[0068] The present invention discloses a 700°C high temperature titanium alloy for medium and short time use, and its microstructure is as follows: Figure 1 As shown, it is a fine lamellar structure of dispersed silicide, which has a smaller grain size and a finer lamellar structure than the microstructure of conventional high-temperature titanium alloy. It shows that through the preparation method of the present invention, that is, the solution treatment above the β phase transformation point and below the silicide dissolution temperature, a fine lamellar structure with dispersed silicide and fine original β grains (original β grains ≤ 500mm, lamellar thickness less than or equal to 5μm) can be successfully obtained.
[0069] The present invention discloses a 700℃ high temperature titanium alloy for medium and short-term use, and its room temperature tensile strength R m ≥1120MPa, yield strength R p0.2 ≥1010MPa, elongation A≥8%, section shrinkage Z≥10%; tensile strength R at 700℃ m ≥610MPa, yield strength R p0.2 ≥470MPa, elongation A≥20%, section shrinkage Z≥64%. Durability at 700℃ / 200MPa is ≥20h, room temperature fracture toughness is ≥35MPa·m 1 / 2 It can not only withstand high temperatures of 700°C, but also has certain medium- and short-term high-temperature durability and fracture toughness. It can meet the urgent needs of high-Mach-number aircraft wings, rudders and other lightweight structural parts for medium- and short-term extreme high-temperature resistance (700°C) high-strength titanium alloys.
[0070] The present invention is further described below with reference to the specification using examples, but the examples are only used for the present invention and are not intended to limit the present invention.
[0071] Example 1
[0072] A 700°C high temperature titanium alloy for medium and short term use, the chemical composition is, by weight percentage, Al: 5.5%, Sn: 3.8%, Zr: 6.5%, Mo: 0.5%, Si: 0.7%, Nb: 0.3%, W: 1.0%, the balance is Ti. The β phase transition point is 1035°C, and the silicide dissolution temperature is 1065°C.
[0073] The alloy is prepared by the following method:
[0074] Step 1: using vacuum consumable melting to melt the alloy ingot three times to obtain an alloy ingot;
[0075] Step 2: subjecting the ingot in step 1 to a first stage deformation;
[0076] Preheat to 900℃ and keep warm for 80min, then heat to 1100℃ and keep warm for 150min, and carry out three-fire open forging. The heating temperature of the first fire is 1150℃, the heating temperature of the second fire is 1100℃, and the heating temperature of the third fire is 1060℃. Each fire deformation is one upsetting and drawing, and the deformation of upsetting and drawing is 45%. Air cooling is performed after forging deformation.
[0077] Step 3: The blank in step 2 is subjected to a second stage of deformation.
[0078] After heating to 1000℃ and keeping temperature for 150min, 5 heat deformations were performed. The deformation before the last heat was one upsetting and drawing, and the deformation of upsetting and drawing was 40%. The last heat was one drawing, and the deformation was 30%. After deformation, it was air-cooled. Finally, a 180mm diameter bar blank was obtained.
[0079] Step 4: The rod segments prepared in step 3 are subjected to solution and aging heat treatment.
[0080] Since the difference between the dissolution temperature of silicide and the β phase transformation point is ≥30°C, the solution treatment temperature is 1055°C, the holding time is 2.5h, and oil quenching is performed; the aging heat treatment temperature is 710°C, the holding time is 5h, and air cooling is performed.
[0081] Example 2
[0082] A 700°C high temperature titanium alloy for medium and short term use, the chemical composition is, by weight percentage, Al: 5.6%, Sn: 3.8%, Zr: 6.0%, Mo: 0.5%, Si: 0.6%, Nb: 0.3%, W: 2%, the balance is Ti. The β phase transition point is 1030°C, and the silicide dissolution temperature is 1055°C.
[0083] The alloy is prepared by the following method:
[0084] Step 1: using vacuum consumable melting to melt the alloy ingot three times to obtain an alloy ingot;
[0085] Step 2: subjecting the ingot in step 1 to a first stage deformation;
[0086] Preheat to 900℃ and keep warm for 80min, then heat to 1050℃ and keep warm for 150min, and carry out 3-fire open forging. The heating temperature of the first fire is 1150℃, the heating temperature of the second fire is 1100℃, and the heating temperature of the third fire is 1050℃. Each fire deformation is one upsetting and drawing. The deformation of upsetting and drawing is 45%, and air cooling is performed after forging deformation.
[0087] Step 3: The blank in step 2 is subjected to a second stage of deformation.
[0088] After heating to 970℃ below the β phase transformation point and keeping the temperature for 150min, the steel was deformed by 5 fires. The deformation before the last fire was upsetting and drawing, and the deformation of upsetting and drawing was 40%. The last fire was drawing, and the deformation was 30%. After deformation, the steel was air-cooled. Finally, a 180mm diameter bar was obtained.
[0089] Step 4: The rod segments prepared in step 3 are subjected to solution and aging heat treatment.
[0090] Since the difference between the dissolution temperature of silicide and the β phase transformation point is between 20 and 30 °C, the solution treatment is: 1040 °C, holding for 2.5 hours, oil quenching, aging treatment: 710 °C, holding for 5 hours, air cooling.
[0091] Example 3
[0092] A 700°C high-temperature titanium alloy for medium and short-term use, the chemical composition is, by weight percentage, Al: 5.6%, Sn: 3.7%, Zr: 5.0%, Mo: 1.0%, Si: 0.6%, Nb: 0.4%, W: 2.0%, and the balance is Ti. The β phase transition point is 1035°C, and the silicide dissolution temperature is 1050°C.
[0093] The alloy is prepared by the following method:
[0094] Step 1: using vacuum consumable melting to melt the alloy ingot three times to obtain an alloy ingot;
[0095] Step 2: subjecting the ingot in step 1 to a first stage deformation;
[0096] Preheat to 900℃ and keep warm for 80min, then heat to 1150℃ and keep warm for 150min, and carry out 4-fire open forging. The heating temperature of the first fire is 1150℃, the heating temperature of the second fire is 1100℃, and the heating temperature of the third and fourth fires is 1060℃. Each fire deformation is one upsetting and drawing, and the deformation of upsetting and drawing is 45%. Air cooling is performed after forging deformation.
[0097] Step 3: The blank in step 2 is subjected to a second stage of deformation.
[0098] After heating to 1000℃ below the β phase transformation point and keeping it for 150min, it is deformed by 6 fires. The deformation before the last 2 fires is one upsetting and drawing, and the deformation of upsetting and drawing is 40%. The deformation before the last fire is one drawing, and the deformation of drawing is 35%. The last fire is die forging, with a deformation of 50%, and the strain rate of die forging is 0.02s -1 Finally, a cake with a diameter of 260×50mm was obtained.
[0099] Step 4: subjecting the cake in step 3 to solution treatment and aging heat treatment.
[0100] Since the difference between the dissolution temperature of silicide and the β phase transformation point is between 20 and 30 °C, the solution treatment is: 1045 °C, holding for 2.5 hours, oil quenching, aging treatment: 710 °C, holding for 5 hours, air cooling.
[0101] Comparative Example 1
[0102] A high-temperature titanium alloy, the preparation method of which is the same as that of embodiments 1 to 3, the only difference being that the chemical composition by weight percentage is Al: 5.6%, Sn: 3.8%, Zr: 3.5%, Mo: 0.5%, Si: 0.55%, Nb: 0.3%, W: 1.0%, and the balance is Ti, which is a traditional titanium alloy composition. The alloy silicide dissolution temperature is 1010 to 1030°C, and solid solution treatment is performed above the phase transition point without silicide.
[0103] Comparative Example 2
[0104] The only difference from Example 1 is that the process method is different. When performing solution and aging heat treatment in step 4, the solution treatment temperature is 1065°C, the holding time is 2.5 hours, and oil quenching is performed; the aging heat treatment temperature is 710°C, the holding time is 5 hours, and air cooling is performed. The solution treatment is performed above the phase transition point at a temperature higher than the dissolution temperature of the silicide.
[0105] Comparative Example 3
[0106] The only difference from Example 1 is that the process method is different. When performing solution and aging heat treatment in step 4, the solution treatment temperature is 1015°C, the holding time is 2.5 hours, and oil quenching; the aging heat treatment temperature is 710°C, the holding time is 5 hours, and air cooling. The solution treatment is performed below the dissolution temperature of the silicide and below the β-transformation temperature.
[0107] Organization and performance testing
[0108] The microstructure of Example 1 is as follows Figure 1 As shown, it is a fine lamellar structure of dispersed silicide (original β grains ≤500mm, lamellar thickness ≤5μm), which has a smaller grain size and finer lamellar structure than conventional high-temperature titanium alloy structure. The white tiny dots in the figure are silicides, which inhibit the growth of grains and make the grains appear as fine lamellar. The microstructure of Examples 2-3 is also a fine lamellar structure of dispersed silicide, with original β grains ≤500mm and lamellar thickness ≤5μm.
[0109] Comparative Example 1 The microstructure is as follows Figure 2As shown, it is a fine lamellar structure with coarse original β grains, and the grain size is generally greater than 650mm. This type of structure has extremely low room temperature plasticity. The grain size of Comparative Example 2 is greater than 650mm, and this type of structure has extremely low room temperature plasticity. The structure type of Comparative Example 3 is a conventional dual-state structure with a high content of silicides. This type of structure has low plasticity and fracture toughness properties.
[0110] The mechanical properties of the embodiments and comparative examples of the present invention are shown in Table 1:
[0111] Table 1
[0112]
[0113]
[0114] It should be noted that when the material elongation A is less than 5% or the cross-sectional shrinkage Z is less than 8% or the room temperature fracture toughness is less than 30 MPa·m 1 / 2 , the plasticity / fracture toughness of the material is low, and usually the plasticity / fracture toughness of the material will be further reduced under high temperature conditions, which is sufficient to show that the short-term high temperature performance of the material is insufficient. Therefore, high temperature performance tests were not performed on Comparative Examples 1 to 3.
[0115] It can be seen from Comparative Example 1 that the alloy of the present invention has obvious advantages over traditional alloys.
[0116] It can be seen from Comparative Examples 2 to 3 that only by performing solution treatment at a temperature higher than the β transition temperature and lower than the silicide dissolution temperature can the original β grain lamellar structure be obtained and the material properties be improved.
[0117] It can be found from the above embodiments that the room temperature tensile strength R m ≥1120MPa, yield strength R p0.2 ≥1010MPa, elongation A≥8%, section shrinkage Z≥10%; tensile strength R at 700℃ m ≥610MPa, yield strength R p0.2 ≥470MPa, elongation A≥20%, section shrinkage Z≥50%. Durability at 700℃ / 200MPa is ≥20h, room temperature fracture toughness is ≥35MPa·m 1 / 2 Therefore, the high-temperature titanium alloy of the present invention can not only withstand a high temperature of 700°C, but also has certain medium- and short-term high-temperature durability and fracture toughness, and can meet the strength and plasticity that are critical for subsequent processing and service.
[0118] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A 700°C high temperature titanium alloy for medium and short term use, characterized in that: The composition includes, by weight percentage, Al: 5.5-6.5%, Sn: 3.0-5.0%, Zr: 5.0-8.0%, Mo: 0.5-1.5%, Nb: 0.2-1.0%, Si: 0.6-0.8%, W: 1.0-2.0%, and the balance is Ti; The medium and short-term use of 700℃ high temperature titanium alloy, room temperature tensile strength R m ≥1120MPa, yield strength R p0.2 ≥1010MPa, elongation A≥8%, section shrinkage Z≥10%; tensile strength R at 700℃ m ≥610MPa, yield strength R p0.2 ≥470MPa, elongation A≥20%, section shrinkage Z≥50%.
2. A method for preparing a 700°C high temperature titanium alloy for medium and short term use, characterized in that: For preparing the 700°C high temperature titanium alloy for medium and short time use as claimed in claim 1, the preparation method comprises the following steps: S1, after vacuum consumable smelting for 3 times, an alloy ingot is obtained; S2, subjecting the alloy ingot to a first stage of deformation; S3, subjecting the alloy ingot to a second stage of deformation; S4, solid solution and aging heat treatment, finally obtain 700℃ high temperature titanium alloy for medium and short time use.
3. The preparation method according to claim 2, characterized in that: In S1, the raw materials added during smelting include, by weight percentage, Al: 5.5-6.5%, Sn: 3.0-5.0%, Zr: 5.0-8.0%, Mo: 0.5-1.5%, Nb: 0.2-1.0%, Si: 0.6-0.8%, W: 1.0-2.0%, and the balance is Ti.
4. The preparation method according to claim 3, characterized in that: In S1, alloy elements Sn, Zr, Mo, Si, Nb, and W are added in the form of intermediate alloys during smelting; the Al portion is brought in by the intermediate alloy, and the insufficient portion is added in the form of high-purity Al beans and Al foils; the insufficient portion of Ti is added in the form of sponge titanium.
5. The preparation method according to claim 2, characterized in that: In S2, the first stage of deformation is to heat the ingot to 20-150°C above the β phase transformation point, keep it warm for a period of time, and then perform 2-4 fires of open forging. Each fire deformation is 1-2 times of upsetting and drawing, and the deformation amount of upsetting and drawing is 30-60%.
6. The preparation method according to claim 5, characterized in that: The β phase transition point is 1030-1045°C.
7. The preparation method according to claim 2, characterized in that: In S3, the second stage of deformation is to heat the ingot to 60-20°C below the β phase transformation point, keep it warm for a period of time, and then perform 2-7 fires of forging or die forging; wherein, the deformation before the last fire is 1-2 times of upsetting and drawing, and the deformation of upsetting and drawing is 30-60%; the last fire is upsetting and drawing, drawing or die forging, and the deformation is 30-70%. If it is die forging, the strain rate should be controlled at 0.01-0.1s -1 , after conversion, they are all air-cooled.
8. The preparation method according to claim 2, characterized in that: In S4, the solution treatment is performed by controlling the solution temperature between the β phase transition point and the silicide dissolution temperature, and the solution temperature is kept for 2 to 5 hours and then water-cooled or oil-quenched; the silicide dissolution temperature is 1050 to 1065°C.
9. The preparation method according to claim 2, characterized in that: In S4, the aging treatment is performed at a temperature of 700-750° C., and the temperature is kept for 5-6 hours before air cooling.
10. The preparation method according to claim 8, characterized in that: In S4, if the difference between the silicide dissolution temperature and the β phase transition point is ≥30°C, the solid solution temperature is selected to be 20°C above the β phase transition point; if the difference between the silicide dissolution temperature and the β phase transition point is between 20 and 30°C, the solid solution temperature is selected to be 10°C above the β phase transition point; if the difference between the silicide dissolution temperature and the β phase transition point is ≤20°C, the solid solution temperature is selected to be 5°C below the silicide dissolution temperature.